Alloimmunization in Pregnancy: Patient-reported Quality of Care, Mental Health Effects, and Impact Upon Daily Life - Sherwood, Molly R.; Weathersby, Bethany M.; Granger, Marion E.; Shanahan, Kathryn A.; Markham, Kara B. (American Journal of Perinatology Reports, 2025)
The purpose of this study was to investigate mental health and impacts upon daily life in patients with a history of pregnancy alloimmunization, and secondarily to examine the relationship between disease severity and quality of care on these outcomes.This was a survey administered between November 2022 and February 2023 to U.S. adults with a history of red cell alloimmunization in pregnancy. Mental health outcomes, quality of care, and daily life impacts were reported.The survey was completed by 127 alloimmunized adults. Anxiety (90.6%), guilt (74.8%), self-doubt (68.0%), isolation (71.4%), depression (68.3%), and symptoms of posttraumatic stress disorder (PTSD) (61.3%) were frequently reported. Mental health support was offered in 24.4%. Respondents reporting a high quality of care in their alloimmunized pregnancies (rating of 8/10 or higher) were significantly less likely than those who perceived receiving lower-quality care to report feelings of guilt (p = 0.0006), self-doubt (p = 0.04), depression (p = 0.03), and symptoms of PTSD (p = 0.001).Despite the pervasive patient burden, mental health support was infrequently offered, and patients reported low satisfaction with continuity of care and their providers' knowledge of alloimmunization. Clinicians interacting with alloimmunized patients must employ a comprehensive patient-centered approach to address the significant disease burden.
Keywords: fetal hydrops; hemolytic anemia; hemolytic disease; isoimmunization; red blood cell antibodies; red cell antibodies; Rh disease; maternal mental health; high risk pregnancy